Any Woman's Blues - Jong, Erica (London Arrow Books, 1990)
Artist, mother and international celebrity Leila Sands is addicted to drink, drugs and her lover. Her hold on sanity slithering away, she embarks on a sensual and spiritual odyssey which takes her, via the wilder shores of lust and licence, to sex-filled, water-lapped days in Venice
Keywords: Romance fiction -- Women